Health on a Cloud: Modeling Digital Flows in an E-health Ecosystem - Stephanie, Felix Lena; Sharma, Ravi S. (Journal of Advances in Management Sciences & Information Systems, 2016)
A unified and well-knit e-health network is one that provides a common platform to its key stakeholders to facilitate a sharing of information with a view to promoting cooperation and maximizing benefits. A promising candidate worthy of being considered for this ponderous job is the emerging ‘cloud technology’ with its offer of computing as a utility, which seems well-suited to foster such a network bringing together diverse players who would otherwise remain fragmented and be unable to reap benefits that accrue from cooperation. The e-health network serves to provide added value to its various stakeholders through syndication, aggregation and distribution of this health information, thereby reducing costs and improving efficiencies. Because such a network is in fact an interconnected ‘network of networks’ that delivers a product or service through both competition and cooperation, it can be thought of as a business ecosystem. . This study attempts to model the digital information flows in an e-health ecosystem and analyze the resulting strategic implications for the key players for whom the rules of the game are bound to change given their interdependent added-values. The ADVISOR framework is deployed to examine the values created and captured in the ecosystem. Based on this analysis, some critical questions that must be addressed as necessary preconditions for an e-Health Cloud, are derived. The paper concludes with the conjecture that “collaboration for value” will replace “competition for revenue” as the new axiom in the health care business that could ideally usher in a fair, efficient and sustainable ecosystem.